Manifestation and Analysis of a 3 Point Lighting System in “The Wedding Party” - Afabor, Henry Kunle (NIU Journal of Humanities; Vol. 8 Núm. 2 (2023): NIU Journal of Humanities, Vol. 8 No. 2, June 2023, 2023)
Having seen the film: “The Wedding Party”, one is challenged to analysis the creative deployment of a 3 point lighting technique in this narrative.  In carrying out a critical examination on the film, the researcher employs the combined methods of a cinematic content/studio analytical approach and a library research method.  This paper is launched with definitions of the key concepts while the synopsis introduces the story in this film.  Findings reveals that the invocation of a 3 point lighting technique in this film is not only meant to guide and concentrate the attention of the viewers on the main characters/actions but deployed to highlight or show the texture of the costume or to distinguish the colours of objects/characters.  It is also meant to reveal the physical actions or facial reactions of the characters in the selected scenes.  The paper equally demonstrates how the key is used as a component of frontal lighting that creates flat looking image on screen; shows how the fill light is employed for mild shading or in modelling the actor’s face.  The paper diagnoses how the backlight helps in revealing the volume rather than creating a flat looking image on screen.  It further demonstrates how the key back light and the fill light are sometimes deployed to create partial silhouette of the images on screen, or used to reveal two levels/planes within a frame where two different actions are occurring concomitantly. Key w ords: A 3 point lighting technique, key light, fill light, backlight, and “The Wedding Party”